Beat: heart monitoring system - Shamsolnizam, Afif Fanshuri; Basri, Iskandar Zulkarnain; Zakaria, Noor Azura; Tajuddin, Taniza; Suryady, Zeldi (2022)
Cardiovascular Diseases (CVD) is a heart and blood disorder that affects people globally. CVD can be chronic if there is no early prevention. Our heart monitoring application, Beat is a personalized heart rate detector using smartphones and smartwatches that aims to assist in preventing CVD through the monitoring of heart rate. Machine learning algorithms were also incorporated into the application. This project shows that the usage of heart rate monitors can be used not only for sports but also in medical fields by alerting heart patients contacts whenever abnormal heart rates are detected. Beat application is a simple, accurate, and low-cost system that uses a smartwatch to detect heart rate and analyze the data on the user's smartphones. Machine learning algorithms were also developed by our team to detect abnormalities in heart rate. This product is suitable for the public especially for the elderly and for patients with heart disease. Therefore, a portable and low-cost health monitor device is achievable without the need for expensive hospital equipment, just by using a smartwatch and this application.